JEJAK EVOLUSI DAN SPESIASI MARGA INDIGOFERA - Muzayyinah, Muzayyinah (BIOEDUKASI, 2012)
ABSTRACT-Initially trace the genealogy of a taxon is an impossibility, when only few parameters available. Many parameters must be taken into account in data collection. Genealogy of plants is much more complicated than other creatures. One of which that believed to trace the genealogy at the same time ensuring that there is speciation in plants is molecular identification, using either chloroplast genomes, mitochondrial genomes and nuclear genomes. Until recently molecular analysis options that address to what, and how Indigofera for the benefit of science.   Keywords: evolution, speciation, Indigofera